Determining Dhap Pokhari lake surface dynamics for restoration strategies through geoelectrical mapping - Anil Kumar Misra; Kuldeep Dutta; Rakesh Kumar Ranjan; Nishchal Wanjari; Subash Dhakal (Water Science)
Lakes in the hilly regions of the Sikkim Himalayas in India are crucial for water supply and tourism. However, this area experiences frequent earthquakes and microtremors, increasing the risk of seismic hazards and contributing to a higher density of subsurface fractures and discontinuities. This has led to water seepage in lakes across Sikkim, turning some from perennial to seasonal. To investigate these issues, geoelectrical mapping techniques, specifically Vertical Electrical Sounding (VES) and profiling, were used to study Dhap Pokhari Lake in Sikkim’s Pakyong district. The findings revealed a subsurface fracture zone beginning at a depth of 20 m and extending down to 50 m. The VES data showed significant variations in sediment thickness and subsurface lithology between two measurement points only 10 m apart, with a noticeable ground settlement of about 2 m at one location. The profiling results indicated a major fracture and two minor ones, which are likely causing water seepage and ground saturation, particularly during rainy seasons, leading to compaction and ground settlement. This poses a risk to the structural stability of the surrounding areas, highlighting the need for effective lake restoration strategies. Geoelectrical mapping is a valuable tool for identifying such subsurface fractures and making evidence-based strategies to revive lakes in this seismically active region.